Rule Creation dan Rule Application Tentang Hari Jadi Nagari dan Batas Nagari di Nagari Panampuang - Frinaldi, Aldri; Susanti, Dessi; Efrina, Rika; Fadhilla, Muthia; Syafril, Rizki (Policy, Law and Political Research Center, 2024)
Panampuang Village has been established since the Dutch colonial era, but the exact time of its establishment cannot be ascertained due to the lack of information and literature. In addition, the issue of the division of the village territory consisting of 7 jorong, which was previously divided into 4 villages, is a classic challenge in determining the boundaries of the village territory. To overcome this problem, it is necessary to create clear village regulations related to the anniversary and boundaries of the village territory (rule create), which are then implemented through socialization and are expected to receive recognition from the community (rule application). The approach method used is participatory training, including preparation, planning, and implementation, with techniques such as games, case studies, practice, brainstorming, discussions, and lectures. This program involves the village government and community elements such as Niniak Mamak, Alim Ulama, Cadiak Pandai, youth, and women. This stage is followed by monitoring to ensure implementation according to plan, as well as evaluation to assess the success of implementing the regulations.